L’espace de la mosquée à Bruxelles : nouveaux liens sociaux et investissement politique - Corinne Torrekens (Revue des Mondes Musulmans et de la Méditerranée)
The Mosque is not only a religious space devoted to worship but a social space and education centre out of which solidarity networks can emerge. How have Muslim religious spaces evolved in the context of the growing Muslim presence among traditional European migratory societies? In the context of European Islam, the traditional role of the mosque has been adapted to new uses as a centre for social solidarity and exchange, cultural activities, sporting events and debates, providing Mosque access for social groups that are traditionally excluded: women, young people and non-muslims. The diversity of roles and populations served has forced the mosque into the political arena as representative of the local Muslim community. By focusing our empirical study on three geographic areas of Brussels, we analyse the process by which heretofore private religious spaces have been opened to the public and given rise to new social practices and linkages, without discounting the debates this evolution supposes.